The entrepreneurial advantage of world cities: evidence from global entrepreneurship monitor data - Zoltán J. Ács; Niels Bosma; Rolf Sternberg (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Recent discussions in the Economic Geography literature increasingly focus on creative cities and the importance of creativity for achieving economic growth. Considering the increased attention on urban areas it is not surprising that the regional dimension of entrepreneurship is a subject of great interest. We set out a framework encompassing the individual process between entrepreneurial perceptions and entrepreneurial activity and demonstrate how the urban environment can have an impact on this process. We create entrepreneurship indices for 34 world cities exploiting the Global Entrepreneurship Monitor (GEM) Database 2001-2006. We investigate differences between the city-level and country-level for a selection of the indices. These exercises can be seen as initial tests of the `entrepreneurial advantage of cities' Based on the literature we expect that most indices will be higher for world cities, although exceptions are also plausible, for instance in world cities where the government resides. Our findings predominantly confirm the entrepreneurial advantage of world cities.
Keywords: R11; M13; O18; 330; Entrepreneurship; world cities; entrepreneurial perceptions; entrepreneurial activity; urbanization; Global Entrepreneurship Monitor; Unternehmer; Stadtökonomik; Urbanisierungseffekt; Welt